Global, regional, and national burdens of cirrhosis in childhood and adolescence during 2000 to 2021: an age-period-cohort analysis - Yang, Xue-Qi; Yang, Xin-Jing; Tian, Yu-Xin; An, Qi; Yao, Yun-Xin; Zuo, Jing; Wu, Bai-Yun; Yang, Jie-Ru; Fan, Yu-Chen (Frontiers in Public Health, 2025)
BackgroundCirrhosis is a major cause of morbidity and mortality worldwide, but data on the cirrhosis burden and trends in children and adolescents are sparse.MethodsData on cirrhosis during 2000–2021, including global-, regional, and national-level numbers of cases, incidence, and prevalence, were collected by the GBD 2021 database. Trends across age groups, periods, and birth cohorts were analysed using the age–period–cohort (APC) model; epidemiological trajectories were predicted using the Bayesian APC (BAPC) model.ResultsFrom 2000 to 2021, cirrhosis incidence decreased in the 5–9 and 10–14-year age groups but increased in the 15–19 and 20–24-year age groups. In the 15–19- and 20-24-year age groups, the respective proportion of cirrhosis due to hepatitis B decreased from 11 to 4% and from 35 to 23%, while the respective proportion due to metabolic dysfunction-associated fatty liver disease (MAFLD) increased from 87 to 93% and from 55 to 67%. Regionally, the proportion of cirrhosis attributable to HBV decreased over time, while MAFLD became the leading cause among individuals aged 15–24 years. Overall, the effects of cirrhosis among children and adolescents were consistent across socio-demographic index regions and globally, increasing with age but decreasing with period and cohort. However, the period and cohort effects of MAFLD-related cirrhosis increased regionally and globally. The BAPC model predicted that the incidence of cirrhosis among children and adolescents will continue to rise until 2050.ConclusionDuring 2000–2021, the burden associated with hepatitis B declined, while the proportion of cirrhosis caused by MAFLD has been steadily increasing. The APC model revealed a consistent global trend of cirrhosis risk, increasing with age but decreasing by period and cohort.